Molecular dynamics simulations reveal structural insights into inhibitor binding modes and mechanism of casein kinase II inhibitors. Issue 5 (24th March 2019) - Ul-Haq, Zaheer; Ashraf, Sajda; Bkhaitan, Majdi M.
Abstract : Casein kinase-II, a member of protein kinase family, plays significant role in different cellular processes such as cell growth, differentiation, proliferation, gene expression, and embryogenesis. Being a potent suppressor of apoptosis, it serves as a significant link for its association with various types of malignancies such as colorectal and breast cancer. To overcome its pathological role in various cancerous diseases, CK-II procures great consideration as a therapeutic target. This study aimed at understanding the binding mechanism and structural properties of benzimidazole derivatives by utilizing various computational tools including docking simulation, three-dimensional quantitative structure activity relationships and molecular dynamic simulation. Structure-based 3D-QSAR techniques such as CoMFA and CoMSIA models, were established from the conformations gained by protein–ligand docking approach. The attained models have showed a good extrapolative power for internal as well as external validation. Moreover, MD simulation was carried out to explain the detailed binding mechanism and the comparison of inhibitor's binding mode with diverse biological activities. A good correlation was observed among docking studies, MD results, and contour map analysis. Interestingly new molecules were designed using detail structural information from MD simulation, showed higher potency of inhibition ( p IC50 7.6–7.7) compare to the most active compound of the series.